Valuing Euro Rating-Triggered Step-Up Telecom Bonds - Patrick Houweling; Albert Mentink; Ton Vorst (Tinbergen Institute, 2003)
We value rating-triggered step-up bonds with three methods: (i) the Jarrow, Lando andTurnbull (1997, JLT) framework, (ii) a similar framework using historical probabilities and(iii) as plain vanilla bonds. We find that the market seems to value single step-up bondsaccording to the JLT model, while it values multiple step-up bonds as plain vanilla bonds.Further, step-up feature market premiums are more volatile than JLT and historical premiums,and the JLT model approximates market premiums always better than the historical method.Finally, most step-up bonds offer a cushion against rating migrations via dampened pricemovements.
Keywords: C13; G12; 330; step-up bonds; Jarrow-Lando-Turnbull model; rating-based reduced form model; transition probabilities.; CAPM; Anleihe; Telekommunikationssektor; EU-Staaten